If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x * x + -8 = 42 Multiply x * x 2x2 + -8 = 42 Reorder the terms: -8 + 2x2 = 42 Solving -8 + 2x2 = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2x2 = 42 + 8 Combine like terms: -8 + 8 = 0 0 + 2x2 = 42 + 8 2x2 = 42 + 8 Combine like terms: 42 + 8 = 50 2x2 = 50 Divide each side by '2'. x2 = 25 Simplifying x2 = 25 Take the square root of each side: x = {-5, 5}
| 2*x=40 | | 21=v(v-4) | | 2xx-8=40 | | 3x^2+7x+13=11 | | 2x-3=64 | | y-.8y=74 | | -5+12=17x-3-16x | | -5x*-3+8= | | 7x+1=-20 | | -5x*3+8= | | -3(x+8)-43=2-42 | | solvex^2=-7x-7 | | 22-x=2x+10 | | 22-x=2(x-5) | | -4-7=-9+x | | -3(x-4)=18 | | 2(5c-1)-1=6c+9 | | 8x+7-5x=-17 | | 6-6(18x-12)=4x | | x^2+25x-150=0 | | 4(2x-4)=9x | | (x-2)-(2-x)= | | 10-5= | | 40+3y-12=13y-14-3y | | -(3y-5)+11= | | (6m-1)2=10 | | 70-2(x+3)=3(x-2) | | 5=9y | | 12(2x-6)+37=3x | | -6(4d+8)= | | 12x-(3x-12)=5+8x | | 2x^3+54= |